Integrating Relational Well-Being into Positive Psychology Approaches to Workplace Conflict - Ntombifuthi Centurion Zwane (Universitas Pattimura, 2026)
The South African public sector is largely grounded in Ubuntu-informed communal values and practices. However, workplace wellness programmes, despite being recognised for enhancing employee well-being and managing workplace conflict, continue to rely predominantly on individualistic Positive Psychology approaches that overlook relational interdependence, shared meaning, and the collective social processes through which conflict is shaped. This study explored how integrating Positive Psychology and Relational Well-Being can strengthen workplace wellness programmes for conflict management in the South African public sector from a social-psychological perspective that foregrounds interpersonal and group-level processes. Although Positive Psychology and Relational Well-Being are often positioned as incompatible, they are complementary theoretical and practical approaches. In a public-sector context shaped by Ubuntu-informed relational norms, their integration enables conflict to be understood as a social-psychological process grounded in interdependence, shared meaning-making, and collective regulation of well-being rather than individual deficit. A systematic literature review synthesising theoretical and empirical social-psychological and organisational research on workplace wellness, relational well-being, and conflict in public-sector contexts was conducted. Findings indicate that while South African public sector wellness programmes are partially informed by Positive Psychology, they show limited alignment with relational well-being approaches, resulting in insufficient attention to interpersonal and group-level sources of conflict. Public sector institutions should adopt integrated wellness frameworks that combine Positive Psychology and Relational Well-Being to promote healthier workplace relationships, reduce conflict, and enhance employee well-being. The study contributes to Social Psychology by recontextualising and extending an established Integrated Well-Being Framework to the domain of conflict management in the South African public sector, demonstrating how relational and culturally grounded processes shape workplace conflict beyond individualistic wellness models.